Synthesis of New series of 1,8-Bis-(4-Aryl Amino Methyl 1,3,4-Oxidiazolyl-5-Thion-2-yl) Octanes, 1,8-Bis-(5-Thio Acetic/ Formic Acid Hydrazide/Acetic Acid 1,3,4-Oxadiazlol-2-yl) Octanes† - Kudari, S.M.; E. Badiger, Sangamesh (Asian Journal of Chemistry, 2010)
Sebacic acid dihydrazide on refluxing with alcoholic potassiumhydroxide and carbon disulphide afforded 1,8-bis-( 1,3,4-oxadiawlyl5-thione-2-yl) octane(II). Compound (II) on reacting withethylchloroformate and ethylchloroacetate yielded the liquid esters(III and IV). The esters thus obtained on reacting with hydrazinehydrate afforded 1,8-bis-(5-thioformic/acetic acid hydrazide 1,3,4-oxadiazol-2-yl) octanes (V and VI). The compound (II) on reactingwith various aromatic amines with formaldehyde yielded 1,8-bis(4-aryl amino methyl 1,3,4-oxadiazol-5-thione-2-yl) octanes (VIIa-1). The compound (II) on further reacting with chloroacetic acidafforded 1,8-bis-(5-thioacetic acid 1,3,4-oxadiazol-2-yl) octane(VIII).